HIV Vaccine Research: The Challenge and the Way Forward - Hai-Bo Wang; Qiu-Hua Mo; Ze Yang (Journal of Immunology Research)
Human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) is a worldwide epidemic, with over 35 million people infected currently. Therefore, the development of a safe and effective HIV-1 vaccine is on top of the global health priority. In the past few years, there have been many promising advances in the prevention of HIV/AIDS, among which the RV144 Thai trial has been encouraging and suggests optimization of the current vaccine strategies or search for novel strategies. Here we reviewed the brief history of HIV-1 vaccine, analyzed key challenges existing now, and illustrated future research priority/directions for a therapeutic or prophylactic HIV-1 vaccine, with the hope of accelerating the speed of vaccine development. We believe that an effective HIV-1 vaccine, together with other prevention approaches, will bring an end to this epidemic in the near future.